MIR‐137 Suppresses Growth and Invasion, is Downregulated in Oligodendroglial Tumors and Targets CSE1L - Li, Kay Ka‐Wai (John Wiley and Sons Inc., 2013)

(untitled) (Brain Pathol)
MicroRNA‐137 (miR‐137) expression has been reported to be decreased in astrocytic tumors in two expression profiling studies but its role in the pathogenesis of oligodendroglial tumors is still limited. In this study, we demonstrate that miR‐137 expression is significantly downregulated in a cohort of 35 oligodendroglial tumors and nine glioma cell lines compared with normal brains. Lower miR‐137 expression is associated with shorter progressive‐free survival and overall survival. Restoration of miR‐137 expression in an oligodendroglial cells TC620, and also glioblastoma cells of U87 and U373 significantly suppressed cell growth, anchorage‐independent growth, as well as invasion. Demethylation and deacetylation treatments resulted in upregulation of miR‐137 expression in TC620 cells. In silico analysis showed that CSE1 chromosome segregation 1‐like (yeast) (CSE1L) is a potential target gene of miR‐137. Luciferase reporter assay demonstrated that miR‐137 negatively regulates CSE1L by interaction between miR‐137 and complementary sequences in the 3′ UTR of CSE1L. Immunohistochemistry revealed that CSE1L is upregulated in oligodendroglial tumors. Knockdown of CSE1L resulted in similar outcomes as overexpressing miR‐137 in oligodendroglioma cells and glioblastoma cells. Overall, our data suggest that miR‐137 regulates growth of glioma cells and targets CSE1L, providing further understanding in the tumorigenesis of gliomas.